Context-Sensitive Ontologies for a Non-reductionist Cognitive Neuroscience. Issue 2 (3rd April 2018) - Dewhurst, Joe
Abstract: The target article criticises reductionist programs in cognitive science for failing to take into account important explanatory features of the organism's physical embodiment and task environment. My aim in this commentary is to show how such features are increasingly being taken seriously by (some) researchers in cognitive neuroscience, who describe the functional activity of neural structures in terms that are context-sensitive rather than intrinsic. This approach can allow us to take seriously the concerns presented in Gallagher's [2019 ] target article without having to completely give up on neuroscientific explanations of human behaviour.